Pulse generator with intermediate inductive storage as a lightning simulator; Review of Scientific Instruments; Vol. 87, iss. 6 - Kovalchuk B. M. Boris Mikhailovich; Kharlov A. V. Anatoly Vasiljevich; Zherlitsyn A. A. Andrey Alekseevich; Kumpyak E. V. Evgeny Valentinovich; Tsoy N. V. Nikolay Viktorovich (2016, 2016)
Title screen